Interannual variability of air-sea CO2 exchange in the Northern Yellow Sea and its underlying mechanisms - Lv, Jia; Nie, Hongtao; Shen, Jiawei; Wei, Hao; Guo, Gang; Zhang, Haiyan (Frontiers in Marine Science, 2024)
A three-dimensional (3-D) physical-biogeochemical-carbon cycle coupled model is used to investigate the interannual variability of the air-sea carbon dioxide (CO2) flux (FCO2) in the Northern Yellow Sea (NYS) from 2009 to 2018. The verification of the model indicate that the simulation results for multiple variables exhibit consistency and fit well with the observed data. The study show that although the multi-year average FCO2 in the NYS is close to the source-sink balance, there are obvious interannual differences between different years. In particular, a relatively strong source of atmospheric CO2 (1.0 mmol m–2 d–1) is exhibited in 2014, while a relatively strong sink of atmospheric CO2 (–0.7 mmol m–2 d–1) emerges in 2016. Mechanism analysis indicates that the abnormally high temperature is the main controlling factor for the relatively high CO2 efflux rate in the NYS in 2014, while the abnormally low dissolved inorganic carbon (DIC) concentration is the main factor contributing to the relatively high CO2 influx rate in 2016. Further analysis reveals that the primary reason for the low DIC concentration since the onset of winter in 2016 is the high net decrease rate of DIC in the NYS in 2015, influenced by net community production in the summer and advection processes during the autumn. The abnormally high primary production during the summer of 2015 results in the excessive reduction of DIC concentration through biological processes. In addition, due to the strong northeasterly wind event in November 2015, low-concentration-DIC water from the Yellow Sea (YS) extends into the Bohai Sea (BS). This further leads to higher DIC flux from the NYS into the BS in the upper mixed layer and increases the inflow of low-concentration-DIC water from the Southern Yellow Sea (SYS) into the NYS. These ultimately result in the abnormal reduction of DIC concentration in the upper mixed layer of the NYS during the autumn of 2015. This study enriches our understanding of interannual variability of FCO2 in the NYS, which will not only help to further reveal the variations of FCO2 under human activities and climate change, but also provide useful information for guiding the comprehensive assessment of the carbon budget.